2008
DOI: 10.2118/95402-pa
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Reservoir Flood-Surveillance Methods Using Streamlines

Abstract: This paper revisits classic flood-surveillance methods applied to injection/production data and demonstrates how such methods can be improved with streamline-based calculations. Classic methods rely on fixed patterns and geometric-based well-rate allocation factors (WAFs). In this paper, we compare conclusions about pattern performance from classic surveillance calculations to conclusions about pattern performance from a streamline surveillance model using flow-based WAFs. We show that very different conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Other assimilation methods employ 'streamline simulation', a computationally efficient reduced-physics simulation method that also allows for rapid assimilation of oil-water fluid fronts; see Datta-Gupta and King (2007) and Batycky et al (2008). Yet another category avoids the explicit modeling of geological parameters and uses a capacitance-resistance representation of well connectivities (Sayarpour et al 2009;Zhao et al 2016), but has not (yet) found widespread application.…”
Section: Application Case Reservoir Engineeringmentioning
confidence: 99%
“…Other assimilation methods employ 'streamline simulation', a computationally efficient reduced-physics simulation method that also allows for rapid assimilation of oil-water fluid fronts; see Datta-Gupta and King (2007) and Batycky et al (2008). Yet another category avoids the explicit modeling of geological parameters and uses a capacitance-resistance representation of well connectivities (Sayarpour et al 2009;Zhao et al 2016), but has not (yet) found widespread application.…”
Section: Application Case Reservoir Engineeringmentioning
confidence: 99%
“…Introducing a standard single-point upwind (SPU) finite-volume discretization results in a reducible, blockstructured linear system Ax ¼ b, which can be solved very efficiently. To illustrate this, we consider Model 2 from the Tenth SPE Comparative Solution Project (Christie and Blunt 2001). This Cartesian box model consists of approximately 1.1 million grid cells and is used widely throughout the literature as a standard benchmark for new simulation methods.…”
Section: Flow Diagnosticsmentioning
confidence: 99%
“…To illustrate how the Lorenz coefficient can be used as a flow proxy for computing recovery factors, we will use 2D horizontal layers of the 3D SPE10 model (Christie and Blunt 2001). This model is highly heterogeneous and will (for unfavorable displacements) give flow patterns with strong fingering effects.…”
Section: Flow Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations